2022
DOI: 10.3389/fbioe.2022.819407
|View full text |Cite
|
Sign up to set email alerts
|

Strontium Ion Removal From Artificial Seawater Using a Combination of Adsorption With Biochar and Precipitation by Blowing CO2 Nanobubble With Neutralization

Abstract: While enjoying the convenience of nuclear energy development, the environmental contamination by radionuclide leakage is of significant concern. Because of its cost-effectiveness and environmental friendliness, biochar has attracted a lot of attention in the field of radioactive water treatment. Herein, a novel teak peel modified biochar (labeled as PMBN3) was prepared and applied to remove strontium from artificial seawater. The characterisation of the prepared PMBN3 showed it contains numerous oxygen-contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 57 publications
(80 reference statements)
0
8
0
Order By: Relevance
“…The presence of both graphite carbon peaks indicates that the material was partially graphitized during pyrolysis, but the main structure remained amorphous carbon. There was no significant difference in the peak positions compared to other carbon materials pretreated with different chemical reagents [35][36][37]. This indicated that phosphoric acid mainly affected the organic composition and pore structure of the material surface but not the crystalline structure.…”
Section: Xrd Analysismentioning
confidence: 81%
“…The presence of both graphite carbon peaks indicates that the material was partially graphitized during pyrolysis, but the main structure remained amorphous carbon. There was no significant difference in the peak positions compared to other carbon materials pretreated with different chemical reagents [35][36][37]. This indicated that phosphoric acid mainly affected the organic composition and pore structure of the material surface but not the crystalline structure.…”
Section: Xrd Analysismentioning
confidence: 81%
“…16 , the linear fitting is shown in Figure 3B , and the fitting correlation coefficient was R 2 = 0.965. Finally, the enthalpy change was calculated as = −1.412 kJ mol −1 , indicating an exothermic reaction; G = −10.474 kJ mol −1 , indicating that the adsorption reaction described as spontaneous; ΔS = 29.89 J·(mol⋅K) −1 , indicating that the disorder degree of solid-liquid interface increased ( Chen and Zhang, 2014 ; Guo et al, 2014 ), and the arrangement of PDA adsorbed on the resin surface was more disordered after adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…Many methods have been attempted to remove strontium ions from solution, such as chemical precipitation, 8 solvent extraction, 9,10 membrane separation 11,12 and adsorption. 13,14 Compared to other methods, adsorption method has a number of advantages, such as simple operation, high removal efficiency and large treatment capacity.…”
Section: Introductionmentioning
confidence: 99%